Flow cytometry study of Escherichia coli treated with plasma-activated water: confirming the absence of the viable but non-culturable state in bacteria - Agus, Rita; Avino, Fabio; Lavrikova, Aleksandra; Myers, Brayden; Furno, Ivo (Frontiers in Microbiology, 2025)
Plasma-activated water (PAW) is an emerging antimicrobial agent with promising applications in bacterial inactivation. The PAW samples are generated by non-contact exposure of deionized water to a surface dielectric barrier discharge plasma and are characterized by a reactive nitrogen species-rich chemistry. In this work, fluorescence flow cytometry is applied to assess the viability of Escherichia coli treated with PAW. The results indicate that PAW exhibits a strong bactericidal effect, significantly increasing propidium iodide positive populations and leading to cell shrinkage. Comparative colony-forming unit counting confirmed these findings, showing agreement between both techniques and ruling out the possibility of a viable but non-culturable (VBNC) bacteria state. These results underscore the potential of the PAW samples produced with the present setup for safe decontamination applications, while also offering insights into the mechanisms of bacterial inactivation.